Phytochemical composition and biological activities of Geranium robertianum L.: a review - Graça, Vânia C. (2016)
Abstract After a period of a certain indifference, in which synthetic compounds were favored, the interest in the study of the biological properties of plants and the active principles responsible for their therapeutic properties has been growing remarkably. Geranium robertianum L., commonly known as Herb Robert or Red Robin, is a spontaneous, herbaceous plant that has been used for a long time in folk medicine of several countries and in herbalism’s practice for the treatment of a variety of ailments. Herein, we present a comprehensive review on the phytochemical characterization and the biological activities of this species, which, accompanying the remarkable increase of its use in herbal medicine, has been disclosed in the literature mainly in the last decade. The phytochemical characterization of G. robertianum has been focused mostly on the investigation of solid-liquid extracts of the plant, with special emphasis on phenolic compounds, particularly flavonoids. Studies concerning the essential oils of this species are still scarce but the number of identified compounds is high. The chemistry of G. robertianum is clearly dominated by phenolic constituents, the most studied classes of compounds being tannins, flavonoids and phenolic acids. The confirmation of the antioxidant, antimicrobial, anti-inflammatory, anti-hyperglycaemic and cytotoxic activities of G. robertianum, closely related to the high content of phenolic compounds, has come to corroborate in some extent the recognized beneficial proprieties of this medicinal plant.